Trends in Contrastive and Error Analysis Research in Arabic Language Education: A Systematic Review (2013–2025) - Latipa, Ucu; Aditya, Viqri; Muslim, Ahmad Bukhori; Koderi, Koderi; Amiruddin, Amiruddin (STAINI Press, 2026)
This study aim to investigates research trends and conceptual developments in contrastive analysis (CA) and error analysis (EA) within Arabic language education from 2013 to 2025 using method a Systematic Literature Review (SLR) approach. Thirty peer-reviewed articles from reputable national and international journals were selected based on inclusion criteria concerning topic relevance, methodological rigor, and empirical contribution. The findings reveal a paradigm shift from structural linguistics toward interdisciplinary approaches integrating psycholinguistic, sociocognitive, and educational technology perspectives. Despite the prevalence of descriptive studies and the limited integration of CA and EA in pedagogy, recent works indicate a growing adoption of data-driven learning and artificial intelligence (AI) tools for automated error detection. This review proposes the Contrastive–Error Diagnostic Framework as an integrative conceptual model linking the predictive and diagnostic dimensions of CA and EA in Arabic language teaching. Limitations include the restricted geographical scope and lack of longitudinal or corpus-based studies. Future research should focus on digital learning analytics to empirically validate the proposed framework and enhance Arabic language pedagogy in the digital era.